Pengaruh Motivasi Terhadap Pemberian Susu Formula Pada Bayi Berat Lahir Rendah - Rany Yulianie (Faletehan Health Journal, 2019)
Exclusive breastfeeding is breastfeeding only including colostrum without any additional. Exclusive breastfeeding for 6 months is a health intervention that has positive impact on reducing IMR. The purpose this study was to determine the effect of knowledge, social support, attitudes and motivation of mothers on formula feeding in Low Birth Weight. This research uses quantitative methods with cross sectional design. The respondents are mothers who have LBW and give formula milk in the working area of ​​Karangpawitan Puskesmas with a total sampling technique of 80 people, collecting data using questionnaires. Analysis technique uses Structural Equation Modeling. The results showed motivation had a significant effect with direct (40.10%) and indirect (0.27%). It was concluded that motivation very influential on formula feeding at LBW. To increase motivation, collaboration between wife, husbands and health workers requires positive stimulation about breast milk so that milk production isn’t hampered and counseling about breast milk.